2010
DOI: 10.1002/ejic.201000879
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Complex Catalyzed Decomposition of Formic Acid

Abstract: Keywords: Platinum / Hydride ligands / Hydrogen storage / C-H activation / Ab initio calculations / Homogeneous catalysis / Formic acid decompositionThe decomposition of formic acid catalyzed by a cationic hydridoplatinum tetradentate phosphane complex was studied by NMR spectroscopy, isotope labeling and DFT calculations.In the initial step dihydrogen is formed by the reaction of the formic acid with the hydrido ligand yielding a platinum formate cation. The formato ligand is then transformed to CO 2 by a β-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…HCOOH ® H 2 + CO 2 (4) HCOOH ® H 2 O + CO (5) For the hydrogen generation, an efficient and selective catalyst is required for the selective decomposition of FA to produce H 2 and avoiding the formation of toxic CO. Nowadays, catalytic efficiency of homogeneous catalysts on the formation of hydrogen via selective decomposition of FA has been significantly improved. [72][73][74][75][76][77][78][79][80][81][82] However, the metal-NP based heterogeneous catalysis has just emerged as an promising method for the selective decomposition of formic acid in purpose of hydrogen generation, although the investigation on this reaction with metal catalysts has already been carried out since 1957. [83][84][85][86][87][88][89][90][91][92] Pd/C based catalysts have been reported as the most selective catalysts for dehydrogenation from the decomposition of FA.…”
Section: Chemical Societymentioning
confidence: 99%
“…HCOOH ® H 2 + CO 2 (4) HCOOH ® H 2 O + CO (5) For the hydrogen generation, an efficient and selective catalyst is required for the selective decomposition of FA to produce H 2 and avoiding the formation of toxic CO. Nowadays, catalytic efficiency of homogeneous catalysts on the formation of hydrogen via selective decomposition of FA has been significantly improved. [72][73][74][75][76][77][78][79][80][81][82] However, the metal-NP based heterogeneous catalysis has just emerged as an promising method for the selective decomposition of formic acid in purpose of hydrogen generation, although the investigation on this reaction with metal catalysts has already been carried out since 1957. [83][84][85][86][87][88][89][90][91][92] Pd/C based catalysts have been reported as the most selective catalysts for dehydrogenation from the decomposition of FA.…”
Section: Chemical Societymentioning
confidence: 99%
“…In the past, a number of research efforts have been devoted to the study of effective catalysts for HCOOH dehydrogenation in which noble metals are usually used, such as Pt [23,24] Pd [25] and Rh [26]. Recent studies showed that highly pure hydrogen without CO could be obtained from HCOOH over soluble organometallic complexes [22,23,27] or insoluble heterogeneous catalysts [28][29][30] in aqueous solution at ambient temperatures. Tedsree et al [31] indicated that Ag nanoparticles coated with a thin layer of Pd atoms can considerably enhance hydrogen production from formic acid at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, HCOOH can be catalytically decomposed according to the dehydrogenation pathway and the dehydration route, depending on the properties of the catalyst used [19][20][21][22]. In the past, a number of research efforts have been devoted to the study of effective catalysts for HCOOH dehydrogenation in which noble metals are usually used, such as Pt [23,24] Pd [25] and Rh [26]. Recent studies showed that highly pure hydrogen without CO could be obtained from HCOOH over soluble organometallic complexes [22,23,27] or insoluble heterogeneous catalysts [28][29][30] in aqueous solution at ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that highly pure hydrogen without CO has been achieved from formic acid with a variety of soluble organometallic complexes or insoluble heterogeneous catalysts in aqueous solution at ambient temperatures. Most of the catalysts used for HCOOH decomposition are based on noble metals, such as Pt, Pd, Au, Ag, Rh, and Ru . For example, recently, Hu et al indicated that Pd and Rh surfaces exhibit high selectivity for decomposition of HCOOH.…”
Section: Introductionmentioning
confidence: 99%